Alfredo Pareja Diezcanseco: apuntes de su itinerario; entrevista (De La Escena Contemporánea) - Ortega, Julio (2014)
In this interview, the result of a meeting that possibly occurred in “the fall of 1984”, Peruvian critic and essayist Julio Ortega develops a comprehensive, entertaining and intense dialogue with novelist, essayist and historian Alfredo Pareja Diezcanseco (Guayaquil, 1908 Quito, 1993), a leading figure of the avant-garde generation known as the Group of Guayaquil, or Generation of the 1930s, in the words of Benjamín Carrión. Ortega offers a journey through the life and work of Pareja Diezcanseco through questions that have to do with his beginnings as a writer, the role of intellectuals in the crossroads of the 30s, politics, the national and Latin American project, his travels at certain times for political reasons and on others for reasons of survival, which led the great Ecuadorian novelist to reside in countries like Chile, México, Argentina and Costa Rica; countries where he learned to cultivate friendships and develop his profession as a storyteller and lecturer. Undoubtedly, this is a dialogue that recuperates, for the historical memory of Ecuador and Latin America, the voice and the word of one of the protagonists of continental literature whose work is inserted in the rich tradition of the twentieth century.